Terapeutas ocupacionais e o Sistema de Atendimento Socioeducativo (SINASE): a prática profissional nas medidas privativas de liberdade - Oliveira, Renata Hoeflich Damaso de (2022)
The socio-educational policy and the National System of Socio-Educational Assistance (SINASE) are constituted with the aim of holding the adolescent responsible for the criminal activity. This system presents different categories of sanctioning measures, ranging from guidance to socio-educational detention of adolescent characterized by deprivation of their liberty. Although confinement is planned as a last resort, juvenile incarceration has been used as an action strategy by the State, considering the number of care units dedicated to the deprivation of the adolescent population's liberty. In the context of confinement, occupational therapists are composing the teams of socio-educational units, even though there is not a significant numerical quantity compared to other professional categories. This research aimed to apprehend, discuss and analyze the occupational therapist's professional practice in socio-educational measures involving deprivation of liberty (provisional confinement, semi-liberty and confinement). The specific objectives are: a) To identify occupational therapists who work in institutions that carry out socio-educational measures of deprivation of liberty; b) Knowing and discussing the theoretical-practical foundation used by professionals working in the socio-educational system; c) Discuss the professional specificity of the occupational therapist in the socio-educational context. The following methodological route was carried out: contacts with managers (state, institutional or local) and service units for mapping and identification of professional occupational therapists linked to socio-educational measures involving deprivation of liberty (n=56), with the subsequent invitation for the resolution of a questionnaire about their practices (participants = 43); six discussion workshops with professionals working on these measures (participants = 09); semi-structured individual interviews with professionals from different Brazilian states (n=04); and holding a meeting to present the results and preliminary analysis categories (participants = 04). The collected data were analyzed based on the discussion of the technician's social function, social occupational therapy and the legislative principles of socio-education. The results, from the different stages, contributed to the identification of characteristics about professionals working at SINASE and their professional practices (routine, theoretical-methodological references, activities, resources and objectives of the intervention process, facilitators and limiters for the function exercises). After data analysis, tensions involving professional practice were discussed with emphasis on understanding the possible practices within the control device, which is the deprivation of liberty unit, added to analyzes about health practices and social action in the socio-educational units and, finally, recognition of professionals as social articulators. In this sense, the collaborators indicated possibilities of occupational therapy as a “space of freedom” within the context of deprivation of liberty. It is concluded that occupational therapists have professional specificity as executors of socio-educational measures of deprivation of liberty, using activities, singular and territorial accompaniments, resources articulation and networks dynamization to contribute with the objectives foreseen in SINASE. The professionals emphasized understanding that the situation of deprivation of liberty, as well as the history of social deprivation which led the adolescents to that specific situation, interfere with the performance of practices aimed at autonomy, emancipation, insertion and social participation of adolescents. The theoretical conception of social occupational therapy was, therefore, a theoretical-methodological subsidy in the objectives achieving.